2017
DOI: 10.1590/1806-9282.63.04.347
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported measures of quality of life and functional capacity in adhesive capsulitis

Abstract: Objective: To evaluate patient-reported measures of quality of life and functional capacity in adhesive capsulitis before and after suprascapular nerve block treatment; to analyze the influence of clinical and sociodemographic variables on both the outcome and correlation between the respective instruments. Method: A prospective clinical study was performed with adhesive capsulitis patients. Inclusion criteria were clinical diagnosis of adhesive capsulitis and a shoulder imaging test. The WHOQOL-BREF and DASH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 28 publications
(52 reference statements)
0
37
0
Order By: Relevance
“…Data on DASH scores in relation to cardiac-related mortality or re-hospitalization were not assessed due to the limited amount of related data that was available. A previous study suggested that the DASH score correlated negatively with the physical, psychological, and environmental WHOQOL-BREF domains in patients adhesive capsulitis [ 21 ]. We also did not evaluate the relationship between other self-reported outcomes, nor do we know the longitudinal changes of these values in cardiac patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data on DASH scores in relation to cardiac-related mortality or re-hospitalization were not assessed due to the limited amount of related data that was available. A previous study suggested that the DASH score correlated negatively with the physical, psychological, and environmental WHOQOL-BREF domains in patients adhesive capsulitis [ 21 ]. We also did not evaluate the relationship between other self-reported outcomes, nor do we know the longitudinal changes of these values in cardiac patients.…”
Section: Discussionmentioning
confidence: 99%
“…Local anaesthetic was used in all 53 studies. Local anaesthetics were used alone in 20 studies, 27 65 and dextrose 61 in a further 5 studies. No study used steroid alone (Fig.…”
Section: Medication Usedmentioning
confidence: 99%
“…We included 53 studies from 14 different countries in this review (Table 1). Of which, 13 studies came from Turkey, [26][27][28][29][30][31][32][33][34][35][36][37][38] 7 each from Australia 20,23,39,38,39,[40][41][42][43] and India, [44][45][46][47][48][49][50] 6 from the United Kingdom, [51][52][53][54][55][56] 4 each from the United States [57][58][59][60] and South Korea, [61][62][63][64] 2 each from Brazil, 65,66 Canada, 67,68 Egypt 69,70 and Italy, 7...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 It can result in detrimental effects on quality of life and the ability to perform activities of daily living (ADLs). 2 It affects 2% to 5% of the global population and is more common in diabetic patients. 3 There are a variety of treatment options available for patients with frozen shoulder as part of the management ladder of interventions.…”
Section: Introductionmentioning
confidence: 99%